THE INFLUENCE OF GREEN COCONUT WATER (COCOS NUCIFERA LINN VARIETY. VIRIDIS) ON THE REDUCTION OF MENSTRUAL PAIN (DYSMENORRHEA) IN FEMALE STUDENTS OF MTSS BABUN NAJAH BANDA ACEH - Desreza, Nanda; Diana, Novi; Masthura, Syarifah (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Menstruation marks the onset of a woman's reproductive phase. Dysmenorrhea is a common issue among young women, often affecting their daily routines. To alleviate dysmenorrhea symptoms, various approaches, both pharmacological and non-pharmacological, have been explored. One such non-pharmacological method involves consuming green coconut water, which is rich in calcium, magnesium, and vitamin C. This research aims to assess the impact of green coconut water (Cocos nucifera Linn variety Viridis) on reducing menstrual pain (dysmenorrhea) among students at Babun Najah Islamic State Junior High School in Banda Aceh. This study employed a quasi-experimental design with a pretest-posttest control group. The research population comprised 65 students, with 15 respondents participating in the study. Data collection took place from May 1st to 20th, 2023. The Wilcoxon test results for the pretest conducted on the first day yielded a mean score of 5.133, while the posttest on the third day resulted in a mean score of 0.733, with a significance value of 0.000, indicating a reduction in menstrual pain. The findings of this research suggest that the consumption of green coconut water (Cocos nucifera Linn variety Viridis) can effectively reduce dysmenorrhea among students at Babun Najah Islamic State Junior High School in Banda Aceh. It is recommended that respondents consider incorporating green coconut water into their routines to alleviate dysmenorrhea pain.